Modelling of corrosion rate in the drinking water distribution network using Design Expert 13 software - Kumar, Saurabh; Singh, Reena; Maurya, Nityanand Singh (Environmental science and pollution research international, 2023)
This study is focused on the modelling of the composite effect of corrosion factors using Design Expert 13 software on the corrosion rate in the water distribution network of Patna (Bihar), India. A total of nine variables, including pH, temperature, total dissolved solid (TDS), alkalinity, calcium hardness, chloride, sulphate, dissolved oxygen (DO) and time, were considered for modelling. The physicochemical parameters were determined through regular monitoring of water samples. The corrosion rate was determined by the direct monitoring of water distribution pipes using adjustments of seven GI coupons for 45, 90, 135, 180, 225, 270 and 315 days. Modelling was performed for various corrosion factors using the low-level and high-level experimental ranges. Nine of the corrosion factors, i.e. pH, temperature, TDS, alkalinity, calcium hardness, chloride, sulphate, DO and time, were considered in this study. The data used for low-level and high-level range were 7.28, 23, 430, 115, 24, 18, 10.94, 3.5 and 0 and 7.86, 28, 704, 284, 180, 98, 38.7, 6.8 and 315, respectively. Using the Box-Behnken design (BBD), 160 runs were conducted, including ten replicates at the central point of each block. The results of ANOVA indicate that the values of R 2 , adjusted R 2 and predicted R 2 are 0.9714, 0.9507 and 0.8941, respectively. The value of R 2 (0.9714) was close to 1, which indicates a good fit. The adequate precision was found to be 30.8442, indicating a good signal. The coefficient of variance discusses reproducibility, and in this case, it was 9.90%. On the basis of the ANOVA result, the quadratic model is well-fitted and can be accepted as a suitable model. A total of seven parameters, such as chloride, sulphate, hardness, alkalinity, pH, calcium and hardness, were used for the design of the experimental corrosion rate (CR). Corrosion rate as observed by direct monitoring of the water distribution system was 1.37, 3.08, 1.90, 1.38, 1.09, 2.05 and 1.45 MPY for 45, 90, 135, 180, 225, 270 and 315 days, respectively. These individual CR versus synthetic aqueous solutions were used to validate the interaction of the response surface. It was observed that the trend of individual corrosion rates in synthetic aqueous solutions and the interaction of composite variables with corrosion rates in a quadratic model of response surfaces were clearly correlated.